Spiritual Leadership of Principals Imbued with Monastic Vows in Malang, Indonesia - Dasrimin, Henderikus (Journal of Asian Orientation in Theology, 2024)
This study aims to describe the implementation of the spiritual leadership of the monks in Catholic schools. The research method used is a descriptive qualitative approach. The research design used a multi-site study conducted at three Catholic Junior High Schools (CJHI) in Malang, East Java, Indonesia. The results of the study show that in developing spiritual leadership in Catholic schools, school principals are imbued with monastic vows namely poverty, chastity and obedience. Embracing monastic vows in leadership assignments has a positive impact on teachers, staff and students.